2010
DOI: 10.1007/s11030-010-9284-z
|View full text |Cite
|
Sign up to set email alerts
|

Traceless synthesis of diketopiperazine fused tetrahydro-β-carbolines on soluble polymer support

Abstract: The Pictet-Spengler reaction, using polyethylene glycol immobilized tryptophan ester with a variety of ketones, was achieved by refluxing condition in acidic chloroform. The linear as well as cyclic ketones were employed. All the ketones were reacted within 6-8 h to furnish soluble polymer-supported tetrahydro-β-carboline in good yields. Further expansion at N-terminus of tetrahydro-β-carbolines was achieved through a reaction with chloroacetyl chloride. Finally, the 2,5-diketopiperazine skeleton was construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the 2011-2015 year range, only two papers concerning an approach in solid phase of the intramolecular P-S reaction appeared [121,122]. In the first one by Chanda et al, polyethylene glycol-immobilized tryptophan ester 102 was combined with a variety of ketones by reflux in acidic chloroform, to give soluble polymer-supported THBCs in good yields [121]. Amination of the N b -chloroacetamide that was obtained by treatment with chloroacetyl chloride, followed by intramolecular cyclization and cleavage of the polymer, finally led to the costruction of a tetracyclic architecture.…”
Section: A New Scenography: Updating the Solid Phase Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2011-2015 year range, only two papers concerning an approach in solid phase of the intramolecular P-S reaction appeared [121,122]. In the first one by Chanda et al, polyethylene glycol-immobilized tryptophan ester 102 was combined with a variety of ketones by reflux in acidic chloroform, to give soluble polymer-supported THBCs in good yields [121]. Amination of the N b -chloroacetamide that was obtained by treatment with chloroacetyl chloride, followed by intramolecular cyclization and cleavage of the polymer, finally led to the costruction of a tetracyclic architecture.…”
Section: A New Scenography: Updating the Solid Phase Strategymentioning
confidence: 99%
“…Amination of the N b -chloroacetamide that was obtained by treatment with chloroacetyl chloride, followed by intramolecular cyclization and cleavage of the polymer, finally led to the costruction of a tetracyclic architecture. The reactions and the following synthesis of biologically promising diketopiperazine-fused THBC structures 103 are resumed in Scheme 29 [121]. of natural products and their analogues [113,114].…”
Section: A New Scenography: Updating the Solid Phase Strategymentioning
confidence: 99%
“…Here, we present a comprehensive overview of the recent progress on bio-landscape and structural diversity of compounds containing proline-based DKP motif, which are exploited as privileged peptidomimetic scaffolds for future innovative drug discovery, smart delivery systems, and modern bio-control agents [34][35][36]. We pay special attention to anticancer proline-based DKPs since cancers are main cause of death all over the world, with nearly 10 million deaths in 2020 according to the WHO [37].…”
Section: Introductionmentioning
confidence: 99%
“…OUCMDZ-1847 [152]. Epicorazine A (112), Epicorazine B (113), Epicorazine C (114), and Exserohilone A (115) were tested for cytotoxic effect against five cancer cell lines: HL-60, HCT-116, A549, K562, and MGC-803 (Table 6, entries [31][32][33][34]. The authors found that Epicorazine A (112) turned out to be the most cytotoxic from the compounds tested with IC 50 values of 0.05 (HL-60), 0.33 (HCT-116), 2.3 (A549), 1.5 (K562), and 2.7 µM (MGC-803) (Table 6, entry 31), and HL-60 cell line was the most susceptible from the lines used in the research.…”
mentioning
confidence: 99%
“…They have attracted attention in recent years because of their broad biological activities [1112] and therapeutic applications, ranging from antibiotics [13] to anticancer agents [14]. Moreover, the DKP moiety has been exploited as a peptidomimetic scaffold [1517]. Structural unification of THBC and DKP pharmacophores has led to new classes of biologically active tetracyclic compounds, both naturally occurring and synthetically made [18].…”
Section: Introductionmentioning
confidence: 99%